PERAN KECERDASAN SPIRITUAL, GAYA HIDUP HEDONIS, KONTROL DIRI DAN RISIKO TOLERAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PADA GENERASI MILENIAL IBU IBU RUMAH TANGGA DI KECAMATAN WULUHAN - Oktavia, Fanda Andini; Supeni, Retno Endah; Wijayantini, Bayu (Relawan Jurnal Indonesia, 2023)
Financial management behavior is important to master because if someone has good financial management behavior then they will be able to balance the money owned or received and the money spent. They possess the ability to manage finances effectively, ensuring they won't fall into monetary hardship. Even if financial issues arise, they're adept at resolving them. Researchers executed a quantitative, descriptive study on 390 housewives in Wuluhan District using questionnaires to gather data. The study revealed that most of the 390 surveyed housewives in Wuluhan District exhibited low spiritual intelligence, a hedonic lifestyle, poor self-control, and high risk tolerance. Multiple regression results indicated a significant impact of spiritual intelligence, hedonic lifestyle, self-control, and risk tolerance on financial management behavior.